Enantiomeric separation of azole antifungal compounds using chromatographic and electrophoretic techniques: a mini review - Nurul Raihana Azhari; Boon, Yih Hui; Nur Nadhirah Mohamad Zain; Faiz Bukhari Mohd Suah; Sharifah Mohamad; Noorfatimah Yahaya; Muggundha Raoov (Penerbit Universiti Kebangsaan Malaysia, 2020)
The separation of azole antifungal chiral compounds has gaining much interests since 1980’s as they possess different biological, pharmaceutical, and pharmacokinetic behaviors at various toxicity levels. Numerous studies have looked into this subject matter, and therefore, this review presents an overview on different chiral separation techniques that have been developed such as liquid chromatography (LC), gas chromatography (GC), supercritical fluid chromatography (SFC), and capillary electrophoresis (CE). This comprehensive review also discusses the mechanisms of the developed analytical methods such as preparation techniques and optimization parameters towards the enantioseparation performances as well as their advantages and drawbacks. Lastly, the conclusion and future directions of the chiral separation, particularly for azole compounds are provided accordingly.